Biopreservation of Paneer using Chitosan - RS, Waghchaure; Khojare, Ajit Shantaramsingh; Jadhav, AB (Indian Journal of Dairy Science, 2022)
The effect of chitosan on microbial, sensory, chemical, and textural characteristics of paneer was investigated for biopreservation and packaging alternatives. Five different concentrations of chitosan solution viz. 0.2%, 0.4%, 0.6%, 0.8%, 1% and three different temperatures viz. 3oC, 20oC and 37oC were selected for the study along with control. Paneer samples coated with 0.8% concentration of chitosan solution observed to bear the least total viable count when compared with other concentrations. Yeast, mold, and coliform count were found nil in all the samples under study. There was no significant difference in the overall acceptability of the paneer samples coated with chitosan solution of different concentrations when subjected to sensory analysis. The proximate compositional analysis viz. moisture, fat, protein, ash, and acidity of the coated pannier samples are reported. Textural analyses of 0.8% chitosan-coated paneer were carried out for the attributes viz. hardness, springiness, adhesiveness, cohesiveness, gumminess, and chewiness and compared with the market samples of paneer.